Inspection and Evaluation of Concrete Pagoda Structure by Non-Destructive Testing - สมบัติ ปฐวี; พุทธวรรณะ สหรัฐ (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Non-destructive testing (NDT) is a reliable method for determining the structural integrity of new and old construction and understanding the conditions of structural defects. It has been acknowledged that the interpretation of non-destructive evaluation has a significant impact on the reliability and consistency of the operator’s knowledge and expertise. Within this era, there has been numerous research and articles upon the topic of Non-destructive Evaluation (NDE); to refine the methodologies or to innovate the existing tools in order for NDTs to be used onsite inspection more frequently. In this paper particularly, we were inquired for evaluating and analyzing the integrity of a pagoda, resistance to loads as well as the true dimensions, located in the temple named “Putha-Jedi” in Kanjanadhit sun-district, Surat Thani district, Thailand, by using the methods of NDT such as Schmidt hammer test, Ultrasonic Pulse Velocity, Ferro scan technique, and more. The parameters acquired will be used for redesigning or strengthening of that pagoda.